2011
DOI: 10.1149/2.031201jes
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Solid State Properties of Anodic Oxides on Magnetron Sputtered Ta, Nb and Ta-Nb Alloys

Abstract: Tantalum oxide, niobium oxide and Ta-Nb containing mixed oxides were grown by anodizing sputter-deposited Ta, Nb and Ta-Nb alloys of different compositions. A photoelectrochemical investigation was performed in order to estimate the band gap and the flat band potential of the oxides as a function of their composition. The band gap of the investigated Ta-Nb containing mixed oxides changed monotonically between those estimated for Ta 2 O 5 (4.1 eV) and Nb 2 O 5 (3.4 eV) and in agreement with a proposed correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 19 publications
3
32
1
Order By: Relevance
“…4, therefore A = 1.35 or A = 2.17 for regular d,d metals and s,p-s,p metals mixed oxides, respectively. In previous papers, [30][31][32] we have shown that conditions such as those mentioned above in the paper of Zunger et al can be encountered in practice in the case of passive films grown on valve-metals alloys where, in suitable electrolytic solutions, the oxide composition maintains the same cation ratio present in the metallic alloy. This is reported in Figures 1-3 for d,d-metals mixed oxides, where the measured optical band gaps as a function of the alloys composition are reported for passive films grown on Ti-Zr and Ta-Nb alloys as well as for physically deposited (Gd x Y (1-x) ) 2 O 3 .…”
Section: Theoretical Backgroundmentioning
confidence: 92%
See 1 more Smart Citation
“…4, therefore A = 1.35 or A = 2.17 for regular d,d metals and s,p-s,p metals mixed oxides, respectively. In previous papers, [30][31][32] we have shown that conditions such as those mentioned above in the paper of Zunger et al can be encountered in practice in the case of passive films grown on valve-metals alloys where, in suitable electrolytic solutions, the oxide composition maintains the same cation ratio present in the metallic alloy. This is reported in Figures 1-3 for d,d-metals mixed oxides, where the measured optical band gaps as a function of the alloys composition are reported for passive films grown on Ti-Zr and Ta-Nb alloys as well as for physically deposited (Gd x Y (1-x) ) 2 O 3 .…”
Section: Theoretical Backgroundmentioning
confidence: 92%
“…This is reported in Figures 1-3 for d,d-metals mixed oxides, where the measured optical band gaps as a function of the alloys composition are reported for passive films grown on Ti-Zr and Ta-Nb alloys as well as for physically deposited (Gd x Y (1-x) ) 2 O 3 . [30][31][32][33][34] The amorphous nature of the passive film on Nb-Ta alloys and the absence of any indirectto-direct optical transition crossover in the case of crystalline films grown on Ti-Zr alloys, allowed testing of the suggestion of Zunger and coworkers 25,26 for the regular semiconducting alloys reported above. Figures 1 and 2 show the dependence of experimental E g values of thin anodic passive films vs alloys composition for Ti-Zr and Ta-Nb mixed oxides.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[8][9][10] Mixing Nb and Ta in their oxidized form during anodization results in extremely interesting behaviors under UV irradiation. 11 Anodic oxides on most valve metals (e.g. Nb and Ta) are amorphous and their crystallization may affect their nal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as disclosed in Figure b, the highest ε ox is measured for the mixed oxide grown on Hf–39 at% Nb alloy (i.e., 45), which is roughly twice the dielectric constant of pure HfO 2 (20) and comparable to the dielectric constant of Nb 2 O 5 (40–50) …”
Section: Resultsmentioning
confidence: 77%